(untitled) (Jurnal Teknologi (Sciences & Engineering), 2020)
Depletion of fossil fuels, concerns on environment, and fuel price fluctuation have become the major drives in searching for sustainable alternative fuel. In that regard, a study was conducted to evaluate the combustion performance of Waste Cooking Oil (WCO) converted into biodiesel and blended with Conventional Diesel Fuel (CDF) as a mean of sustainable replacement for diesel fuel. In this study, the production of biodiesel fuel from waste cooking oil was done via transesterification process, using the single step approach. The properties of the WCO biodiesel was characterized. The combustion performance of the produced fuels has been studied for B10 and B30 biodiesel from WCO and CDF (as baseline) based on their wall temperature profiles and gaseous emissions generated such as nitrogen oxides (NOx), carbon monoxide (CO) and sulphur dioxide (SO2). It was found that the B30 WCO biodiesel emits lower emission compared to CDF but at the same time generates a lower temperature profile.